The Influence Of The Game Of Snakes And Ladders On Mathematics Learning Outcomes In The Independent Curriculum Class Ii - Friska, Sonia Yulia; Marini, Arita; Zakiah, Linda (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
This research aims to determine whether there is a significant influence of the use of the snakes and ladders game on the mathematics learning outcomes of class II students at SD Negeri 21 Pulau Punjung. Due to the fact that there are still many students' mathematics learning outcomes that have not yet reached the KKM. This is due to the lack of use of media in the learning process so that students feel bored and passive in class. This research aims to determine the influence of the Snakes and Ladders Game on Independent Mathematics Learning Outcomes for Class II Students at SD Negeri 21 Pulau Punjung. This type of research is quantitative research using a pre-experimental design (non-design). The type of design used by researchers is one-group-pretest-posttest-design. This research was conducted at SD Negeri 21 Pulau Punjung. Based on the results of the paired sample test, a significance value of 0.000 0.05 was obtained. It can be concluded that there is an influence of the snakes and ladders game on Merdeka class II mathematics learning outcomes at SD Negeri 21 Pulau Punjung. Based on research, the snakes and ladders game has a good influence on students' mathematics learning outcomes. Teachers can use the snakes and ladders game to make students more active and can improve student learning outcomes.